Pengaruh Konten Tutorial Kecantikan di Instagram Terhadap Minat Beli Kosmetik Wajah pada Mahasiswi Tata Rias dan Kecantikan Universitas Negeri Padang - Rahmadani Vildira; Siska Miga Dewi (Tamasya : Jurnal Pariwisata Indonesia, 2024)
The rise of digital media, particularly social media like Instagram, has transformed how beauty products are marketed and consumed. This research aims to investigate the influence of beauty tutorial video content on Instagram on the purchasing interest of cosmetic products among students in the Department of Beauty and Makeup Education at Universitas Negeri Padang. A quantitative methodology was employed, involving a sample of 31 respondents who completed a structured questionnaire. The findings revealed a significant positive correlation between the video content and purchase interest, indicating that engaging tutorial content effectively drives students' interest in buying cosmetic products. This study contributes to understanding the impact of social media marketing on consumer behavior in the beauty industry and suggests that brands leverage such platforms to enhance consumer engagement and sales. The implication of this research is to assess the extent to which beauty tutorial content on Instagram influences the purchasing interest in facial cosmetics among students in the Department of Beauty and Makeup Education at Universitas Negeri Padang. Therefore, it aims to provide insight into how significantly beauty tutorial content on Instagram affects the purchasing interest in facial cosmetics among students in the Department of Beauty and Makeup Education at Universitas Negeri Padang.